Grafting relations in atemoya (Annona x atemoya Mabb.) plants: Peroxidase and phenolic compounds - Baron, Daniel; Amaro, Amanda Cristina Esteves [UNESP]; Macedo, Ana Claudia [UNESP]; Dalanhol, Samanta Jaqueline [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP]; Ferreira, Gisela [UNESP] (Southern Cross Publishing, 2018)
The aim of this study was to evaluate if variations in the peroxidase activity (PRX) and the phenolic compounds (PC) concentration in atemoya scion (Annona x atemoya Mabb.) grafted onto different rootstocks are related to incompatibility. The experiment was conducted in a greenhouse, with atemoya scion grafted onto Annona species rootstocks [A. emarginata 'var. terra-fria'; A. emarginata 'var. mirim; A. mucosa and atemoya (homograft)] and these species ungrafted. The evaluations were performed at 30 and 60 days after grafting (DAG) in the hypocotyl region, where the grafting was performed, in each grafting combination and the same region corresponding to the stem tissue in ungrafted plants. The atemoya scion grafted onto A. mucosa showed higher PRX than A. mucosa ungrafted, although smaller than A. emarginata 'var. mirim' rootstock. In atemoya grafted onto A. emarginata 'var. fria' rootstock, no significant change in PRX compared to A. emarginata 'var. fria', atemoya ungrafted and homograft. The PC concentration at 30 DAG showed no significant differences in the grafted plants, although higher than in their respective ungrafted. At 60 DAG, no differences between grafted plants were observed, however, the PC concentrations in atemoya grafted onto A. emarginata 'var. terra-fria' and 'var. mirim' rootstocks were higher than those observed in A. emarginata 'var. terra-fria' and 'var. mirim' ungrafted, respectively. We concluded that variations in PRX and the PC are not related or triggered to incompatibility between atemoya scion grafted onto A. emarginata 'var. terra-fria', 'var. mirim' and A. mucosa.
Keywords: Annonaceae; Incompatibility; Plant biochemistry; Plant physiology; Plant propagation